(untitled) (Research, Society and Development, 2022)
The present study aimed to investigate the circulation of arbovirus in symptomatic individuals with acute febrile syndrome and jaundice treated in the Municipalities of Parauapebas and Canaã de Carajás, from 2008 to 2010. The database was generated from the application of clinical questionnaires -epidemiological investigations in the Municipalities of Parauapebas and Canaã de Carajás carried out by the Evandro Chagas Institute from 2008 to 2010 with the aim of carrying out the epidemiological investigation of arboviruses in these regions that suffer anthropogenic actions. Sociodemographic data (age, sex and occupation) and laboratory results from virological methods, such as viral isolation in cell culture, and serological methods such as hemagglutination inhibition and the enzyme immunoassay for capturing IgM antibodies, were analyzed, separated into two groups, one with acute febrile syndrome and the other with icteric febrile syndrome, which generated a database with information on 707 individuals containing 1172 samples already processed. Regarding the socio-demographic profile, the age group of the most prevalent individuals was 5 to 14 years old in the two syndromes studied. The male sex was more frequent, and the febrile jaundice syndrome stood out with a higher prevalence with about 59%. Taking into account the occupation, it was found that the Medium Level Technician was the most common. In the laboratory results, 968 (82.6%) had total antibodies through Hemagglutination Inhibition for Flavivirus, Alphavirus and Orthobunyavirus genera. It was possible to observe the statistical difference in the frequency of Arboviruses in the studied groups, p<0.05 between the syndromes. In the ELISA result, IgM antibodies to Dengue, Yellow Fever and Oropouche virus were detected. In the viral isolation through the C6/36 cell, Dengue virus serotypes 1 and 2 and Mayaro virus were isolated, evidencing the acute phase of the infection in the patients, demonstrating the active circulation of the viruses in these areas. Therefore, monitoring the circulation of arboviruses in populations living in areas of environmental transformation is extremely important, as it allows the assessment of the emergence or re-emergence of arboviruses.